Sistem Deteksi Posisi Dan Pengambilan Bola Pada Robot Sepak Bola - Amperawan, Amperawan; Andika, Destra; Anisah, Masayu; I.J, Marcelinus (Universitas PGRI Palembang, 2022)
One of the robot contests held in Indonesia at regional and national levels is the Indonesia Sepal Bola Robot Contest (KRSBI) with wheels, which is a part of the Indonesian Robot ContestÂ which is a design and engineering competition in the field of robotics. KRSBI in 2017 is a new division organized by RISTEKDIKTI with the theme